ANALISIS SIFAT MEKANIK DAN DAYA SERAP AIR MATERIAL KOMPOSIT SERAT ROTAN - Franklin Donald Izaak; Fentje Abdul Rauf; Romels Cresano Apelles Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
The aim of this research is to obtain the optimum tensile strenght of rattan fiber composite for different volume fraction of fiber and resin. without treatment, and find result of fracture at the specimens. Material used in this research is rattan fiber which have a straight fiber orientation. Different volume fraction without treatment used in this study. The composites was molded with epoxy used as matrix. Tensile test was performed based on ASTM D638 standard. Maximum tensile test obtained is 197.505 N / mm at 30% volume fraction of epoxy and 70% fiber, While the optimum water absorption is 2.71 grams of at 90% volume fraction of epoxy and 10% fiber. Keywords : rattan fiber, epoxy, tensile test, water absorption